Analisis Kelayakan Finansial Usaha Jamu Bubuk Instan Cak Emon Ganding Kabupaten Sumenep - Adinda Nurfitriah; Ika Fatmawati; Dody Tri Kurniawan (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
This research aims to determine and analyze whether the Cak Emon instant herbal medicine powder business in East Gaddu Village, Ganding District, Sumenep Regency, is feasible to continue and also to see the effect of sensitivity changes in the rise in the cost of red ginger essential components and the decline in output of Cak Emon instant herbal medicine powder on the feasibility of the Cak Emon instant herbal medicine powder business. The research location was determined purposively. The research was conducted from October 2023 to April 2024. The approach taken for data analysis is a tool to analyze the feasibility of the financial aspect, namely investment criteria and sensitivity analysis with the switching value method. The findings of this business feasibility analysis indicate that the NPV value is IDR. 137,398,571,-; Net B/C value of 1,82; IRR value of 31,85%; and the Payback Period value of 2.31 years (2 years and three months). Thus, it can be said that the Cak Emon instant herbal medicine powder business is profitable and worthy of continuing. Meanwhile, this business is worth continuing in the scenario of the sensitivity analysis's findings about the price of red ginger raw materials by 40%. However, for the sensitivity analysis scenario on a production decline of 23%, the outcomes of the investment criteria show that this business is no longer feasible.